PEMOLAAN KOMUNIKASI TRADISI BASIACUANG SEBAGAI BENTUK KEARIFAN LOKAL DALAM UPACARA PERNIKAHAN MASYARAKAT MELAYU KAMPAR PROVINSI RIAU (Studi Etnografi Komunikasi Tradisi Basiacuang di Desa Kuok Kecamatan Kouk Kabupaten Kampar) - Kurnia Husmiwati; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Basiacuang tradition in the village of Kuok is a custom part and the oral tradition inherited Kampar Malay community for generations of ancestors embraced therein previous values and norms in Kampar Malay community life. This study aims to determine patterning Basiacuang as a Form of Communication Tradition Local Wisdom in Kampar Malay wedding ceremony Society Riau Province. To achieve these objectives it raised questions about how the situation of communication in basiacuang tradition. Basiacuang communication events in tradition, and follow in the tradition basiacuang communication in the Village District of Kuok Kuok Kampar District of Riau ProvinceThis type of research is qualitative. While research method used is an ethnographic study of communication. Most of the data were collected through observation and interviews. Informen earned by 8 people. Five people who existed as Ninik Mamak tribal chief (speakers), and three people are public figures. By using purposive sampling technique. After the interviews, participant observation, field notes, literature studies, documentation and internet searching. Keabsahaan test data by triangulation and the extension of participation.The results obtained useful to know basiacuang patterning tradition communication as a form of local keariafan in Kampar Malay wedding ceremony in the village community Kuok Kuok Kampar District of Riau Province in conveying the object and purpose of a particular moment in the deliberations conducted by Ninik Mamak indigenous tribal chief among parties family men (those who come) with the woman's family (the waiting) to seek and reach a mutual agreement to continue the relationship nephew kejenjang more serious or marriage. In marriage basiacuang aims to surrender child Ninik Mamak nephew of male to female Ninik Mamak .Keywords : basiacuang tradition in the wedding ceremony Kampar Malay community , tradition , ethnography of communication